Vedolizumab exposure in pregnancy: outcomes from clinical studies in inflammatory bowel disease. Issue 7 (7th February 2017) - Mahadevan, U.; Vermeire, S.; Lasch, K.; Abhyankar, B.; Bhayat, F.; Blake, A.; Dubinsky, M.
Summary: Background: Vedolizumab is a gut‐selective immunoglobulin G1 monoclonal antibody to α4 β7 integrin for the treatment of Crohn's disease (CD) and ulcerative colitis (UC). Prospective clinical studies of vedolizumab in pregnancy have not been conducted; therefore, existing safety data of vedolizumab in pregnancy were examined. Aim: To assess pregnancy outcomes in females and partners of males who received vedolizumab. Methods: All pregnancy data collected during the clinical programme (from 14 May 2007 to 27 June 2013) and in the post‐marketing setting (to 19 November 2015) were analysed. Results: Across six studies, there were 27 pregnancies in female participants and 19 pregnancies in partners of male participants. Among 24 vedolizumab‐treated females (23 with CD/UC, one healthy volunteer), there were 11 live births, five elective terminations, four spontaneous abortions and four undocumented outcomes. A congenital corpus callosum agenesis anomaly was reported in one live birth from a healthy volunteer with extensive obstetric history exposed to single‐dose vedolizumab 79 days before estimated conception. Of 19 pregnancies in partners of male participants, there were 11 live births, two spontaneous abortions, three elective terminations and three undocumented outcomes. Post‐marketing reports recorded 81 pregnancies, resulting in four live births, 11 spontaneous abortions and 66 pregnancies that were on‐going or reported undocumented outcomes. Conclusions: Initial analysis, limited by sample size and follow‐up, identified no new safety concerns for pregnancy outcomes in females directly or indirectly exposed to vedolizumab. However, vedolizumab should be used during pregnancy only if the benefits to the mother outweigh the risks to the mother/unborn child. Abstract : Linked Content This article is linked to Shim and Seow, Mahadevan et al and Julsgaard et al papers. To view these articles visithttps://doi.org/10.1111/apt.14027, https://doi.org/10.1111/apt.14054, https://doi.org/10.1111/apt.14837 andhttps://doi.org/10.1111/apt.14855 .